2021
DOI: 10.1021/acs.macromol.1c02077
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Conformations and Surface Charge Regulation of Spherical Polymer Brushes in Stretched Regimes

Abstract: In the present work, we study the equilibrium conformations of linear polyelectrolytes tethered onto a spherical, oppositely charged core in equilibrium with an ionic reservoir of fixed concentration. Particular focus is placed on the situation of stretched chains, where the monomer concentration is known to display an inverse square-law decay far away from the spherical surface, which is then further extrapolated all the way down to the grafting core. While the equilibrium distributions of mobile ions are com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…On this basis of a lot of work on theoretical simulations of single-component polymer grafted nanoparticles, 22,61,62,[64][65][66][67][68][69][70][71][72][73] theoretical simulations of two-component polymer grafted nanoparticles has also gradually attracted attention. Koski et al 12 used the theoretically-informed Langevin dynamics (TILD) to study the self-assembly of nanoparticles modified with different polymers to form different structures of vesicle, droplet and dispersed, respectively (Fig.…”
Section: Different Polymer Chain-modified Nanoparticlesmentioning
confidence: 99%
“…On this basis of a lot of work on theoretical simulations of single-component polymer grafted nanoparticles, 22,61,62,[64][65][66][67][68][69][70][71][72][73] theoretical simulations of two-component polymer grafted nanoparticles has also gradually attracted attention. Koski et al 12 used the theoretically-informed Langevin dynamics (TILD) to study the self-assembly of nanoparticles modified with different polymers to form different structures of vesicle, droplet and dispersed, respectively (Fig.…”
Section: Different Polymer Chain-modified Nanoparticlesmentioning
confidence: 99%
“…The Baxter model of protonation also showed that there is a change in equilibrium constant when an acidic group is moved from bulk to the surface [38][39][40][41] . In general, the renormalization of the equilibrium constant is due to the broken rotational and translational symmetry at the surface compared to the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed PB theory is known to be very accurate for suspensions with monovalent 1:1 electrolytes. However recent works, based on Baxter's model of sticky spheres to describe protoa) Electronic mail: bakhshandeh.amin@gmail.com b) Electronic mail: derek.frydel@usm.cl c) Electronic mail: levin@if.ufrgs.br nation/deprotonation equilibrium, showed [38][39][40][41] that discreteness of surface groups affects significantly the effective charge predicted by the NP theory. The importance of ion polarizability and of finite ion size was also explored in reference 42 .…”
Section: Introductionmentioning
confidence: 99%
“…The Baxter model of protonation also showed that there is a change in equilibrium constant when an acidic group is moved from bulk to the surface. Generally, the renormalization of the equilibrium constant is due to the broken rotational and translational symmetry at the surface, compared to the bulk. However, the theory developed showed that both the discrete charge effects and the renormalization of the bulk equilibrium constant by the surface can be included within the NP framework.…”
Section: Introductionmentioning
confidence: 99%
“…The NP approach is based on Poisson–Boltzmann (PB) theory, which neglects the discrete nature of colloidal surface groups and electrostatic correlation effects. Indeed, PB theory is known to be very accurate for suspensions with monovalent 1:1 electrolytes. However, recent works, based on Baxter’s model of sticky spheres to describe protonation/deprotonation equilibrium, showed that discreteness of surface groups significantly affects the effective charge predicted by the NP theory. The importance of ion polarizability and of finite ion size was also explored in ref .…”
Section: Introductionmentioning
confidence: 99%